1995
DOI: 10.1002/jat.2550150404
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to jp‐8 jet fuel alters pulmonary function and substance p levels in fischer 344 rats

Abstract: In a simulated military flightline exposure protocol, Fischer 344 rats (F344) were used to investigate the pulmonary effects of JP-8 jet fuel inhalation. Exposures were nose only and for 1 h daily. Groups were exposed for 7 days (7D) or 28 days (28D). Each exposure group had a matched longitudinal control group (LC7 and LC28). Exposure concentrations of 520 mg m-3 caused an increase in dynamic compliance after 7 days of exposure, but compliance changes were not seen with continued exposure (28D, 495 mg m-3). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 11 publications
1
43
2
1
Order By: Relevance
“…Examination of the lungs with a light microscope did not reveal any adverse findings. A NOAEC was not obtained (Pfaff et al 1995).…”
Section: Studies With Aerosolmentioning
confidence: 97%
“…Examination of the lungs with a light microscope did not reveal any adverse findings. A NOAEC was not obtained (Pfaff et al 1995).…”
Section: Studies With Aerosolmentioning
confidence: 97%
“…Morphological evaluation after acute JP-8 aerosol exposures showed lesions following a range of doses up to 113 mg/m 3 (4,17,19). Subsequent in vitro experiments in our labs explored the role of epithelial barrier function upon JP-8 exposure.…”
Section: Morphological Evaluation-histology and Micrographymentioning
confidence: 99%
“…Initial in vivo experiments in our labs revealed that aerosol exposure results in the targeting of distal airways as shown by enhanced respiratory permeability to 99m TcDTPA (4,17,18). Morphological evaluation after acute JP-8 aerosol exposures showed lesions following a range of doses up to 113 mg/m 3 (4,17,19).…”
Section: Morphological Evaluation-histology and Micrographymentioning
confidence: 99%
“…Past studies have linked JP-8 exposure to a multitude of adverse health effects including developmental, hepatic, immunological, neurological, pulmonary, and dermal effects (Cooper and Mattie, 1996;Dossing et al, 1985;Harris et al, 1997;Smith et al, 1997;Pfaff et al, 1995;Ullrich, 1999). However, perhaps of greatest importance are the effects of JP-8 jet fuel on the respiratory system and consequently, pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…On a physiological level, several studies have demonstrated deleterious effects on pulmonary function including increased pulmonary resistance and increased respiratory permeability (Robledo and Witten, 1998). On a cellular level, pathological changes including interstitial edema, injured alveolar septa, damaged bronchiolar epithelium and alveolar type II cells, and epithelial necrosis have also been observed, indicating significant cellular damage as a result of JP-8 exposure Pfaff et al, 1995;Robledo and Witten, 1998;Robledo et al, 2000). On a biochemical level, altered expression of certain chemical mediators has also been observed, including macrophage inflammatory protein-2 (MIP-2), tumor necrosis factor-alpha (TNF-α), and anti-inflammatory mediator prostaglandin E 2 (PGE 2 ) (Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%